Effects of montmorency tart cherry (L. Prunus Cerasus) consumption on nitric oxide biomarkers and exercise performance. (16th April 2018) - Keane, K. M.; Bailey, S. J.; Vanhatalo, A.; Jones, A. M.; Howatson, G.
Abstract : The purpose of this study was to investigate the effects of Montmorency tart cherry juice (MC) on nitric oxide (NO) biomarkers, vascular function, and exercise performance. In a randomized, double‐blind, placebo (PLA)‐controlled, crossover study, 10 trained cyclists (mean ± SD; V ˙ O2peak 59.0 ± 7.0 mL/kg/min) acutely ingested 30 mL of either MC or PLA following dietary restrictions of polyphenol‐rich compounds and completed 6‐minutes moderate‐ and severe‐intensity cycling bouts 1.5 hour post‐ingestion on 2 occasions for each experimental condition. The severe‐intensity cycling test was continued to exhaustion on 1 occasion and immediately followed by a 60‐seconds all‐out sprint on the other occasion. Blood pressure, pulse wave measures, tissue oxygenation index, and plasma nitrite concentration were assessed pre‐ and 1.5 hour post‐ingestion. Time to exhaustion was not different between conditions ( P > .05), but peak power over the first 20 seconds (363 ± 42 vs 330 ± 26 W) and total work completed during the 60‐seconds all‐out sprint (21 ± 3 vs 19 ± 3 kJ) were 10% higher in the MC trial compared to the PLA trial ( P < .05). Systolic blood pressure was 5 ± 2 mm Hg lower 1.5 hour post‐MC supplementation compared to PLA supplementation ( P < .05). There were no differences in pulse wave measures, plasma nitrite concentration, or tissue oxygenation between the MC and PLA trials ( P > .05). These results suggest that acute supplementation with MC can lower blood pressure and improve some aspects of exercise performance, specifically end‐sprint performance, in trained cyclists.